Moving lab-grown tissues into the clinic: organ-on-a-chip and bioengineered skin systems - Reed-McBain, Catherine A.; Patel, Janmesh D.; Reed-McBain, Finnbar L. K.; Al-Adra, David; Virumbrales-Muñoz, María; Ayuso, Jose M. (Frontiers in Lab on a Chip Technologies, 2024)
For patients with end stage organ failure, organ transplant is frequently the only curative option available. However, organs available for transplant are in critically short supply around the world, which has led to lengthy wait times and increased mortality. Increased global life expectancy, coupled with raised age thresholds for recipients, has heightened demand and further compounded the need for alternative strategies. Bioengineering substitutes including organ-on-a-chip and 3D bioprinting technologies have made considerable strides toward whole organ generation. Skin is the organ where the most advances have been made thus far, due to the relatively less complex spatial architecture and industry interest in the development of sophisticated models for pharmaceutical and cosmetics testing. Here, we discuss the challenges of recapitulating the complexity of native skin, including a stratified structure, vascularization, and inclusion of skin appendages, such as hair follicles and sweat glands. We discuss current technological and biological progress in the field of tissue and organ bioengineering as well as highlight future challenges to generate de novo tissue for skin grafting.